Participation in an action research project on vaccine services for children: relationship with vaccine delays - Mariejka Beauregard; Nicholas Brousseau; Manale Ouakki; Marilou Kiely; Chantal Sauvageau; Paule Clément; Maryse Guay (Taylor & Francis Group, 2020)
Multicomponent interventions are effective in improving vaccine coverage. However, few studies have assessed their effect on timely vaccination. The aim of this study was to compare the proportion of children with vaccine delays at 2- and 12-month visits according to whether or not health centers have participated in an action research project on the organization of vaccination services for 0-5-year-olds. The action research project included a multicomponent intervention and was conducted between 2011 and 2015 in Quebec, Canada. An ecological before/after design was used for this analysis. A total of 264,579 DTaP-IPV-Hib (2-month visits) and 240,541 Men-C-C (12-month visits) vaccine doses were administered during 2011-2012 to 2014-2015 fiscal years, including 19% in 14 participating health centers and the remaining in 78 nonparticipating centers. Vaccine delays demonstrated a more pronounced decreasing trend in participating versus nonparticipating health centers (p < .0001 at 2 and 12 months). Between 2011-2012 and 2014-2015, participating centers managed to eliminate 35% of their vaccine delays at 2-month visits and 33% at 12-month visits, whereas nonparticipating centers eliminated 19% of delays at both visits. Our results are consistent with a positive impact of the multicomponent intervention, despite the fact that it had not specifically aimed at decreasing vaccine delays.